In Situ Catalytic Hydrogenation of Biomass‐Derived Methyl Levulinate to γ‐Valerolactone in Methanol. Issue 9 (14th April 2015) - Tang, Xing; Li, Zheng; Zeng, Xianhai; Jiang, Yetao; Liu, Shijie; Lei, Tingzhou; Sun, Yong; Lin, Lu
Abstract In this work, the hydrocyclization of methyl levulinate (ML) to γ‐valerolactone (GVL) was performed in MeOH over an in situ prepared nanocopper catalyst without external H2. This nanocopper catalyst served as a dual‐functional catalyst for both hydrogen production by MeOH reforming and hydrogenation of ML. Nearly quantitative ML conversion with a GVL selectivity of 87.6 % was achieved at 240 °C in 1 h in MeOH under a nitrogen atmosphere. ML in the methanolysis products of cellulose also could be hydrogenated effectively to GVL over this nanocopper catalyst even in the presence of humins to give an ML conversion of 94.1 % and a GVL selectivity of 73.2 % at 240 °C in 4 h. The absorption behavior of humins on the surface of the nanocopper catalyst was observed, which resulted in a pronounced increase in the acidic sites of the nanocopper catalyst that facilitate ring‐opening and the hydrocarboxylation/alkoxycarbonylation of GVL to byproducts.